2009
DOI: 10.1093/aob/mcp097
|View full text |Cite
|
Sign up to set email alerts
|

Phytoliths in woody plants from the Miombo woodlands of Mozambique

Abstract: The first quantitative taxonomy of phytoliths from Miombos is presented here, including new types and constituting the most extensive phytolith key for any African ecoregion. Evidence is presented that local woody species are hypervariable silica producers and their phytolith morphotypes are highly polymorphic. The taxonomic significance of these phytoliths is largely poor, but there are important exceptions that include the morphotypes produced by members from >10 families and orders. The typical phytolithic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
117
1
8

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(129 citation statements)
references
References 43 publications
3
117
1
8
Order By: Relevance
“…produces tracheids and rugulose spheres of about 20-24 µm diameter and Mammea siamensis tiny spheres of 4 µm diameter. In accordance with our results, MERCADER et al (2009) reported the production of globular psilate phytoliths in leaves, but not in the stems of the Clusiaceae family.…”
Section: B) Scrub Communitysupporting
confidence: 93%
See 1 more Smart Citation
“…produces tracheids and rugulose spheres of about 20-24 µm diameter and Mammea siamensis tiny spheres of 4 µm diameter. In accordance with our results, MERCADER et al (2009) reported the production of globular psilate phytoliths in leaves, but not in the stems of the Clusiaceae family.…”
Section: B) Scrub Communitysupporting
confidence: 93%
“…Some species were studied and the results are variable. MERCADER et al (2009) observed the presence of globular granulate opal phytoliths in species of the family; and bilobate, polylobate, rondel and elongate phytoliths were observed in Anisotome antípoda, A. latifolia and Stilbocarpa polaris (THORN, 2004). Furthermore, WALLIS (2003) found no opal phytoliths in Trachymene didiscoides and T. oleracea.…”
Section: D) Shrub Vegetation On the Margins Of Maricá Lagoon Communitymentioning
confidence: 97%
“…Phytolith extraction and biogenic silica content (bSi) measurements were accomplished through the dry-ashing technique based on the methodological guidelines published by Albert and Weiner [27] and Mercader et al [28,29]. The ashes were mixed thoroughly, then mounted on light microscope slides in immersion oil and observed with a Zeiss Axioskop 2+ microscope at a magnification of 1000×.…”
Section: Laboratory Procedures and Data Analysismentioning
confidence: 99%
“…Five shoots of each specimen were compounded and treated as 1 sample. Phytolith extraction from the leaf blades and leaf sheaths was accomplished through dry ashing (Albert and Weiner, 2001) based on Mercader (2009Mercader ( , 2010. The mass of the leaves was weighed before and after drying, then the mass of the ash was weighed before and after adding a hydrochloric (HCl) and nitric acid (HNO 3 ) (1:1) solution Phytoliths (500-600 per specimen) were counted in adjacent but not overlapping lines across the cover slip (22 mm in width and length).…”
Section: Methodsmentioning
confidence: 99%